The Influence of Local Own Revenue on Community Economic Growth in Bandungan District - Alex Jefferson; Mohamad Halilintar (Yayasan Adra Karima Hubbi, 2024)
This study aims to analyze the influence of Local Own Revenue (PAD) on economic growth in Bandungan District, a region with significant potential, especially from the tourism and local business sectors. Data were collected through questionnaires involving 50 respondents, consisting of community members, business actors, and tourists. The analysis results indicate that PAD has a positive and significant relationship with economic growth, with a correlation coefficient of 0.67. A simple linear regression test revealed that every one-unit increase in PAD would increase economic growth by 0.55 units, and 45 percent of the variation in economic growth can be explained by PAD. The Kolmogorov-Smirnov test ensured that the data are normally distributed, making the regression model valid and a sound basis for conclusions. Overall, PAD has proven to be an important factor in driving economic activities in Bandungan District, although other factors such as investment, economic policies, and infrastructure are also needed to achieve optimal growth. The optimization of PAD by the regional government is expected to strengthen the local economy and improve the welfare of the community in the region.